THE NATIONAL DRESS AS A SYMBOL OF IDENTITY: HARMONY OF TRADITION AND MODERN AESTHETICS IN FASHION DESIGN (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
The national costume of a people is more than just a traditional garment; it is a visual expression of cultural identity, historical continuity, and aesthetic philosophy. This article explores the symbolic and functional significance of Uzbek traditional dress as a marker of national identity, tracing its evolution from ancient customs to contemporary fashion design. Rooted in centuries of craftsmanship, folklore, and regional diversity, the national attire embodies intricate embroidery, vibrant colors, and silhouette structures that mirror the beliefs, rituals, and socio-cultural codes of the Uzbek people. The research investigates how modern fashion designers in Uzbekistan and beyond reinterpret these traditional elements to create contemporary clothing that maintains its ethnic authenticity while appealing to global aesthetic trends. It emphasizes the role of fashion as a cultural bridge, where heritage and innovation meet, creating styles that speak to both local values and international audiences. Special attention is paid to the integration of traditional ornamentation, handwoven fabrics, and symbolic motifs into present-day collections, showcasing how ancestral designs continue to inspire modern creativity.This article also discusses the cultural diplomacy function of national dress in international arenas, such as fashion weeks, cultural exhibitions, and tourism campaigns. Through qualitative analysis and visual documentation, the study affirms that the preservation and creative adaptation of national costume design serve as a powerful instrument in maintaining cultural heritage and promoting a sense of belonging among the younger generation. Ultimately, Uzbek national dress is presented not merely as historical relics but as a living art form that harmonizes memory, identity, and modernity.